The role of instrumental guanxi in the relation between entrepreneurs' social competence and firms' financial performance: A comparative study. Issue 1 (1st January 2021) - Bari, Muhammad Waseem; Mahmood, Faiq; Qurrah-tul-ain,; Bashir, Mohsin; Usman, Muhammad
Abstract: Even though many studies have examined the role of instrumental guanxi in the formation and development of entrepreneurship, how instrumental guanxi and social competence support entrepreneurs in enhancing firm financial performance (FFP) has not been investigated. Thus, this study investigates the relationship between entrepreneurs' social competence and FFP in the textile industry of China and Pakistan to examine how instrumental guanxi mediates the said relationship. In Studies 1 and 2, 251 Chinese and 270 Pakistani entrepreneurs, respectively, were randomly selected. The partial least square structural equation modelling approach was employed to evaluate the data. In Study 1, social perception, impression management, and expressiveness have a positive and significant impact on FFP. Moreover, instrumental guanxi partially mediates the impact of all dimensions of social competence except social perception. In Study 2, impression management, persuasiveness, and expressiveness have a positive and significant impact on FFP, and instrumental guanxi partially mediates the impact of social adaptability on FFP. Given the competitive advantage theory, both groups of entrepreneurs can mutually support and enhance their social competence as well as FFP.